Motivation and Turnover Intention of Information Technology Employees in Vietnam. - NGUYEN, HONG NHUNG (2020)
Background - Much research indicates that turnover results in demotivated employees, lowering productivity and organisational reputation. Besides, the IT labour force shortage and turnover are becoming emergent challenges and causing negatively to individuals and organisations’ operation in Vietnam.